Vitamin D status indicators in indigenous populations in East Africa - Luxwolda, Martine F.; Kuipers, Remko S.; Kema, Ido P.; van der Veer, E.; Dijck-Brouwer, D. A. Janneke; Muskiet, Frits A. J. (European journal of nutrition, 2013)
Purpose Sufficient vitamin D status may be defined as the evolutionary established circulating 25-hydroxyvitamin D [25(OH)D] matching our Paleolithic genome. Methods We studied serum 25(OH)D [defined as 25(OH)D 2 + 25(OH)D 3 ] and its determinants in 5 East African ethnical groups across the life cycle: Maasai (MA) and Hadzabe (HA) with traditional life styles and low fish intakes, and people from Same (SA; intermediate fish), Sengerema (SE; high fish), and Ukerewe (UK; high fish). Samples derived from non-pregnant adults (MA, HA, SE), pregnant women (MA, SA, SE), mother–infant couples at delivery (UK), infants at delivery and their lactating mothers at 3 days (MA, SA, SE), and lactating mothers at 3 months postpartum (SA, SE). Erythrocyte docosahexaenoic acid (RBC-DHA) was determined as a proxy for fish intake. Results The mean ± SD 25(OH)D of non-pregnant adults and cord serum were 106.8 ± 28.4 and 79.9 ± 26.4 nmol/L, respectively. Pregnancy, delivery, ethnicity (which we used as a proxy for sunlight exposure), RBC-DHA, and age were the determinants of 25(OH)D. 25(OH)D increased slightly with age. RBC-DHA was positively related to 25(OH)D, notably 25(OH)D 2 . Pregnant MA (147.7 vs. 118.3) and SE (141.9 vs. 89.0) had higher 25(OH)D than non-pregnant counterparts (MA, SE). Infant 25(OH)D at delivery in Ukerewe was about 65 % of maternal 25(OH)D. Conclusions Our ancient 25(OH)D amounted to about 115 nmol/L and sunlight exposure, rather than fish intake, was the principal determinant. The fetoplacental unit was exposed to high 25(OH)D, possibly by maternal vitamin D mobilization from adipose tissue, reduced insulin sensitivity, trapping by vitamin D-binding protein, diminished deactivation, or some combination.